2006
DOI: 10.1038/sj.ejcn.1602464
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol-enriched oolong tea increases fecal lipid excretion

Abstract: Objective: To assess possibility of polyphenol-enriched oolong tea to reduce dietary lipid absorption in humans. Design: Twelve healthy adult subjects, three males and nine females, aged (mean7s.d.) 22.071.8 years, respectively, were randomly divided into two groups. The participants were followed a double-blind placebo-controlled crossover design, including 7-day washout periods and 10-day treatment periods. During the treatment periods, subjects were given about 38 g of lipids from potato chips (19 g each wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
58
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 36 publications
2
58
0
Order By: Relevance
“…It has been reported that lipid excretion in feces increased by the administration of oolong tea polyphenols. 16) In the polyphenol study, fecal lipid concentration (estimated from the reported data) seemed to stay in similar levels as shown in our current study, suggesting a possibility that there may be some upper limit for fecal lipid concentration while keeping normal fecal shape and conditions.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…It has been reported that lipid excretion in feces increased by the administration of oolong tea polyphenols. 16) In the polyphenol study, fecal lipid concentration (estimated from the reported data) seemed to stay in similar levels as shown in our current study, suggesting a possibility that there may be some upper limit for fecal lipid concentration while keeping normal fecal shape and conditions.…”
Section: Discussionsupporting
confidence: 59%
“…Polyphenols have been reported to suppress postprandial elevation of triacylglycerol by promoting lipid excretion into feces, 15,16) so we considered that RMD would also have a similar function; promotion of lipid excretion. We conducted the animal and human experiments to confirm the effect of RMD on the lipid excretion into feces.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we determined in a human study that polyphenol-enriched oolong tea increased lipid excretion into the feces when subjects took a high lipid diet. 25) These findings confirm that oolong tea and OTPP inhibited dietary fat absorption in the intestine by inhibiting pancreatic lipase activity.…”
Section: Discussionsupporting
confidence: 76%
“…176 Some published data suggest that extract-induced fecal lipid excretion is associated with reductions in weight gain and changes in TG metabolism, 97,177 while other studies report no significant correlations. 178 The lack of effects found in some studies could be due to compensatory increases in lipase secretion similar to those seen in studies on condensed tannins in rats.…”
mentioning
confidence: 98%